2005
DOI: 10.1001/archpsyc.62.10.1089
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Hypomania in 908 Patients With Bipolar Disorder Evaluated Prospectively in the Stanley Foundation Bipolar Treatment Network

Abstract: Mixed hypomania is common in patients with symptoms of hypomania and particularly common in women. Potential overlap of clinical symptom scales should be assessed before study of patients with bipolar disorder symptoms is undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
122
2
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(133 citation statements)
references
References 42 publications
5
122
2
4
Order By: Relevance
“…This does not mean that these symptoms are always bipolar, only that a bipolar nature is more likely than not in mood disorders (a bipolar nature of irritability and psychomotor agitation in psychotic disorders is expected to be unlikely). The bipolar nature of mixed depression (of which irritability, psychomotor agitation, and distractibility are among the most frequent symptoms) was supported by BP family history (odds ratio = 3.3; controlling for BP-II = 2.4) by a dose-response relationship between the number of intradepression hypomanic symptoms and BP family history loading [38, 47, 48, 61], by finding factors of mania/hypomania in mixed depression [37, 55, 56,71,72,73], and by finding MDE in hypomania [53, 60, 62]. While depression is common in many axis I and axis II disorders, mania and hypomania are more specific of BP [3, 74, 75].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not mean that these symptoms are always bipolar, only that a bipolar nature is more likely than not in mood disorders (a bipolar nature of irritability and psychomotor agitation in psychotic disorders is expected to be unlikely). The bipolar nature of mixed depression (of which irritability, psychomotor agitation, and distractibility are among the most frequent symptoms) was supported by BP family history (odds ratio = 3.3; controlling for BP-II = 2.4) by a dose-response relationship between the number of intradepression hypomanic symptoms and BP family history loading [38, 47, 48, 61], by finding factors of mania/hypomania in mixed depression [37, 55, 56,71,72,73], and by finding MDE in hypomania [53, 60, 62]. While depression is common in many axis I and axis II disorders, mania and hypomania are more specific of BP [3, 74, 75].…”
Section: Resultsmentioning
confidence: 99%
“…There are descriptions of mixed depression in Falret’s ‘circular insanity’ [39], Hecker’s ‘cyclothymia’ [40], and in Kraepelin’s ‘manic-depressive insanity’ [3]. Mixed depression has recently been described in BP-I, BP-II, and MDD [35, 38,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. Frequency of mixed depression, defined as an MDE plus at least 2 or 3 noneuphoric manic/hypomanic symptoms, was up to 70% in BP, and up to 30% in MDD.…”
Section: Resultsmentioning
confidence: 99%
“…While most studies agree that MxD has worse outcomes than non-MxD and is less responsive to, or even worsened by, common antidepressant treatments [24,25,26,27,28,29,30,31], one recent large study found that the likelihood of remission was greater in depressive patients with DSM-5 mixed features treated with antidepressants [32]. However, data on this topic are limited [7,33,34,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, a recent large systematic investigation of the nature of hypomania suggests that hypomania is often mixed with depressed mood, especially in women. 27 This quality of hypomania tends to be expressed as activated or agitated depression and may further hinder bipolar recognition.…”
Section: Dsm-ivmentioning
confidence: 99%